Taking test and treat interventions to the next level: Beginning to think what additional information needs to guide public health and operational decisions? - (:unkn) unknown (My University, 2013)
BackgroundThe proposition universal repeat HIV testing and early initiation of antiretroviral treatment for all HIV-positives (UTT) can lead to reduced HIV incidence is being, or will be, tested in several studies. UTT interventions are major social, as well as biomedical interventions, for individuals and target communities. Implementing UTT trial (ANRS 12249 TasP Trial) provoked thinking about what is needed for public health and operational decisions to move to the next level if UTT efficacy is demonstrated.MethodsIn ANRS 12249 Tasp Trial innovative social science tools are implemented at each UTT stage to ensure a comprehensive understanding of the social determinants of intervention uptake at the individual and community-level and the impacts at individual, household and community level. But these alone cannot guide such a decision.ResultsAdditional questions requiring answers:Social and Behavioural consequences of UTT: What are the long-term social and behavioural consequences of large numbers of people knowing their HIV-status and starting treatment early? Will impacts on sexual behaviour, disclosure and stigma necessarily be positive, now and in the long term?Changes in individual and community norms: Will community perceptions of HIV and healthcare be changed seeing healthy people going to clinics? How are community norms around testing and treatment, stigma and discrimination affected by prolonged, intense research? Can salient positive changes be identified and replicated?Operational and ethical implications of moving UTT into routine care: Who should lead? What are the sustainability requirements? What ethical issues are there in authorities ‘knowing’ individuals’ HIV status and care uptake?ConclusionsUTT strategies have potentially great social consequences for the individuals and populations involved. Questions emerging from UTT trials need further enquiry before public health and operational decisions to move beyond the trials are
Keywords: African Research